Hypoglycaemia in hospitalised neonatal calves: Prevalence, associated conditions and impact on prognosis. (November 2016) - Trefz, F.M.; Feist, M.; Lorenz, I.
Highlights: This study assessed the clinical and prognostic relevance of severe hypoglycaemia in 10, 060 neonatal hospitalised calves. The prevalence of severe hypoglycaemia on admission to the hospital was 6.3%. Severe hypoglycaemia was associated with a poor survival rate of 20.6%, compared to 74% in calves with normoglycaemia. Severe hypoglycaemia was associated with evidence of septicaemia, hypothermia, malnutrition, and generalised peritonitis. Abstract: Hypoglycaemia has traditionally been associated with neonatal diarrhoea and endotoxaemia in calves, but the clinical relevance of this finding in spontaneously diseased calves has not previously been evaluated. To determine the prevalence and prognostic relevance of severe hypoglycaemia (plasma glucose concentration < 2 mmol/L), data from 10, 060 hospitalised calves (≤21 days of age) were retrospectively analysed. Additionally, clinical findings and diagnoses in a subset of 100 calves with severe hypoglycaemia were compared with those in 100 randomly selected calves with initial plasma glucose concentrations in the reference range (4.4–6.9 mmol/L). The prevalence of severe hypoglycaemia in the whole study sample was 6.3%. Severe hypoglycaemia was associated with a poor survival rate of 20.6% vs. 74.0% discharged animals in the group of calves with initial normoglycaemia. Review of medical records revealed that severe hypoglycaemia was significantly associated with clinical or necropsy evidence of septicaemia, hypothermia, history or clinical evidence of malnutrition, and peritonitis of varied origin, but not with the presence of neonatal diarrhoea. Only 10 of 100 calves with severe hypoglycaemia showed central nervous involvement such as seizures and opisthotonus. In conclusion, severe hypoglycaemia has a low prevalence in diseased calves in a hospital setting, but is associated with serious health problems and therefore a high risk of non-survival. Severe hypoglycaemia was not easily diagnosed based on clinical signs, but should be suspected in calves with clinical evidence of septicaemia, hypothermia, acute abdominal emergencies, and a history or clinical evidence of malnutrition.